The ecological agriculture as a political position in the current model for colombian agrarian development (2005)
Some characteristics of the model green revolution are discussed from an environmental point of view, understood as the study of the complex relationships between environment and culture. They include variables of social organization such as the level of soil stress, climate and earth surface, they also include symbolic structures like land accessibility and technological and scientific power of the societies where the model was originated. Some aspects of technology transfer are reviewed as well as the process of the new transgenic model, which is opposed to the alternative agricultural movements. Some qualms on the pertinence of the models for the solution of the central problems of the Colombian agriculture are presented.